Influence of the Afghan drug traffic on the system of regional security of Central Asia (Journal of Philosophy Culture and Political Science, 2019)
Nowadays one of the topical issues the international community faces is illegal traffic in drugs. Transportation of drugs becomes the reason of growth of organized crime, corruption, violence, threatens safety of the states and has an impact on development of the international community. The research of a problem of the Afghan drug traffic is relevant as it constitutes danger not only on a national level, but also at the regional and international levels, promotes distribution of terrorism, extremism and religious radicalism. In this regard, in article prerequisites of the Afghan drug traffic, the level of their distribution in the states of Central Asia and the factors influencing it are analyzed, the degree of threat to the Afghan drug traffic is defined on regional security. On the basis of consideration of prerequisites of the Afghan drug production the reasons of transformation of the state into the center of a narcoturn,a branch of drug traffic in the certain countries of the region and their influence on a social and economiccondition of neighboring countries are analyzed. Authors carried out the statistical analysis of acondition of drug traffic in the region on the basis of historical, comparative, causal and retrospectivemethods of a research. Also authors note importance of holding actions of the regional organizations forfight against the Afghan drug traffic. During the research this problem in the system of regional securityis comprehensively considered, works of national, Russian, Central Asian and western researchers areused. Special attention is paid to the factors influencing the reasons of transformation of the Afghan drugtraffic into a problem of the regional level, the effectiveness of joint actions of the countries of the regionin permission of this problem is noted.Key words: drug traffic, Afghan factor, regional security, regional policy, regional organizations.